Thermal processing of canned nata de coco in syrup - Bustria, Medard Marie M.; Sy, Stella J. (1995)
Process calculation was computed based on the heat penetration parameters determined for nata de coco in syrup in 307 x 409 cans (fh = 82.15; fc = 21.09; jch = 0.62; jcc = 0.95; Tih = 168.35) and the thermal resistance characteristic of Cl. pasteurianum (212 = 0.5 min; z = 16 F). The process schedule at 212 F of nata de coco in syrup packed in 307 x 409 and 603 x 700 UGL cans was computed to be 30 mins. and 39 mins. respectively. Pilot scale production runs using one gallon cans were conducted using the calculated process. Results of the microbiological analysis indicated that the calculated process employed was adequate. The general acceptability of the product was described as "like slightly".
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Nata de coco